Debt Seniority and Sovereign Debt Crises - Ari, Anil (IMF Working Papers; Working Paper ;, 2018)
Is the seniority structure of sovereign debt neutral for a government's decision between defaulting and raising surpluses? In this paper, we address this question using a model of debt crises where a discretionary government endogenously chooses distortionary taxation and whether to apply an optimal haircut to bondholders. We show that when the size of senior tranches is small, a version of the Modigliani-Miller theorem holds: tranching just redistributes government revenues from junior to senior bondholders, while taxes and government borrowing costs remain unchanged. However, as senior tranches become sufficiently large, default costs on senior debt transpire into a stronger commitment to repay not only the senior tranche, but also the junior one. We show that there is a lower threshold for senior bonds above which tranching can eliminate default on both junior and senior debt, and an upper threshold beyond which the government defaults also on senior debt.